Antihypertensive action of soluble epoxide hydrolase inhibition in Ren‐2 transgenic rats is mediated by suppression of the intrarenal renin–angiotensin system. (30th March 2013) - Varcabova, Sarka; Huskova, Zuzana; Kramer, Herbert J; Hwang, Sung Hee; Hammock, Bruce D; Imig, John D; Kitada, Kento; Cervenka, Ludek
Summary The aim of the present study was to evaluate the hypothesis that the antihypertensive effects of inhibition of soluble epoxide hydrolase (sEH) are mediated by increased intrarenal availability of epoxyeicosatrienoic acids (EETs), with consequent improvement in renal haemodynamic autoregulatory efficiency and the pressure–natriuresis relationship. Ren‐2 transgenic rats (TGR), a model of angiotensin (Ang) II‐dependent hypertension, and normotensive transgene‐negative Hannover Sprague–Dawley (HanSD) rats were treated with the sEH inhibitor cis‐4‐(4‐(3‐adamantan‐1‐yl‐ureido)cyclohexyloxy)benzoic acid (c‐AUCB; 26 mg/L) for 48 h. Then, the effects on blood pressure (BP), autoregulation of renal blood flow (RBF) and glomerular filtration rate (GFR), and on the pressure–natriuresis relationship in response to stepwise reductions in renal arterial pressure (RAP) were determined. Treatment with c‐AUCB did not significantly change BP, renal autoregulation or pressure‐natriuresis in normotensive HanSD rats. In contrast, c‐AUCB treatment significantly reduced BP, increased intrarenal bioavailability of EETs and significantly suppressed AngII levels in TGR. However, treatment with c‐AUCB did not significantly improve the autoregulatory efficiency of RBF and GFR in response to reductions of RAP and to restore the blunted pressure–natriuresis relationship in TGR. Together, the data indicate that the antihypertensive actions of sEH inhibition in TGR are predominantly mediated via significant suppression of intrarenal renin–angiotensin system activity.